Detection of spatiotemporal variation in ranavirus distribution using eDNA. Issue 2 (27th November 2019) - Vilaça, Sibelle Torres; Grant, Samantha A.; Beaty, Lynne; Brunetti, Craig R.; Congram, Megan; Murray, Dennis L.; Wilson, Chris C.; Kyle, Christopher J.
Abstract: Amphibian population declines have been associated with emerging diseases including ranaviruses, which can cause mass die‐offs across entire amphibian communities. Understanding and mitigating disease spread requires knowledge of spatial and temporal patterns of pathogen distribution, but also how environmental factors influence pathogen occurrence. We applied environmental DNA (eDNA) detection tools to survey spatial and temporal distributions of ranaviruses by sampling 103 waterbodies in southeastern Ontario, Canada and assessed the role of abiotic factors as predictors of pathogen occurrence. Ten waterbodies sampled during June–August (>30 km between sites) revealed that ranavirus was marginally more prevalent ( p  = .055) during the latter part of the summer. Ninety‐three sites sampled at a finer scale (<10 km between sites) exhibited seasonal variability in ranavirus detection (site prevalence: 56% May; 66% July). Occupancy modeling revealed that wetland size and elevation influenced ranavirus occurrence while sampling date and water temperature influenced probability of detection. These findings indicate that biotic factors, such as host density and alternative hosts, should be investigated further as likely determinants of ranavirus prevalence across the landscape. Further, these results highlight the sensitivity of eDNA for detecting widespread presence of ranavirus and that abiotic factors may have a limited role in determining its prevalence and infectivity. Abstract : We investigated the presence of ranaviruses in wetlands in Ontario, Canada by using eDNA. Our results showed a widespread presence of ranavirus in southern Ontario with seasonal variability. Habitat occupancy modeling showed that wetland size influenced ranavirus occupancy while sampling date influenced the probability of detection.